Ex-situ biogas upgrading in thermophilic up-flow reactors: The effect of different gas diffusers and gas retention times. (November 2021) - Ghofrani-Isfahani, Parisa; Tsapekos, Panagiotis; Peprah, Maria; Kougias, Panagiotis; Zhu, Xinyu; Kovalovszki, Adam; Zervas, Athanasios; Zha, Xiao; Jacobsen, Carsten S.; Angelidaki, Irini
Highlights: Biological biogas upgrading process was evaluated in up-flow reactors. Different types of gas distributers were investigated for biogas upgrading. Biogas with more than 98% CH4 was produced in ex-situ biogas upgrading process. H2 gas–liquid mass transfer rate can be improved using porous SiC gas distributor. Abstract: Four different types of ceramic gas distributors (Al2 O3 of 1.2 μm and SiC of 0.5, 7 and 14 μm) were evaluated to increase biomethane formation during ex-situ biogas upgrading process. Each type of gas diffuser was tested independently at three different gas retention times of 10, 5 and 2.5 h, at thermophilic conditions. CH4 production rate increased by increasing input gas flow rate for all type of distributors, whereas CH4 concentration declined. Reactors equipped with SiC gas distributors effectively improved biomethane content fulfilling natural gas standards. Microbial analysis showed high abundance of hydrogenotrophic methanogens and proliferated syntrophic bacteria, i.e. syntrophic acetate oxidizers and homoacetogens, confirming the effect of H2 to alternate anaerobic digestion microbiome and enhance hydrogenotrophic methanogenesis. A detailed anaerobic bioconversion model was adapted to simulate the operation of the R1 -R4 reactors. The model was shown to be effective for the simulation of biogas upgrading process in up-flow reactors.